(3GdcGed aj HMhK GdJShjbs - (3gdGd(B, (3HOQ GdOjfs ((3YeGfs (3OGQ RgQGfs, 2002)
(3ebOeI h eONd Gdi HMhK GdJShjb h GdJWQb Gdi HMhK GdJShjb h GJNGP GdbQGQGJ eY JfGhd fXe GdeYdheGJ GdJShjbjI h cPG JUeje h GLQGAGJ GdHMK GdJShjbj h GSJNOGe GdeYdheGJ GdJShjbjI aj GNJjGQ GdbQGQGJ Gh GdHOGFd GdefGSHI HGSJNOGe fXQjI HjR ddbQGQGJ h GdJWQb Gdi GdJLQHI GdYdejI h GdHjGfGJ h WQb GdMUhd Ydi GdHjGfGJ GdChdjI h GdeTGgOI h GdbjGS h SdGde GdbjGS h CNjQG GdYjfGJ h GdJMdjd (B.s
Keywords: (3GdJShjb (B- (3HMhKs